Global dynamics of SIR model with switched transmission rate - Chladná, Zuzana; Kopfová, Jana; Rachinskii, Dmitrii; Rouf, Samiha C (Journal of mathematical biology, 2020)
We propose a new epidemiological model, based on the classical SIR model, taking additionally into account a switching prevention strategy. The model has two distinct thresholds that determine the beginning and the end of an intervention and two different transmission rates. We study the global dynamics of the proposed two-dimensional model.
Keywords: lineární modely; kontrola infekčních nemocí; vakcinace; Humans; Mathematical Concepts; Disease prevention; SIR model dynamics; Vaccination; základní reprodukční číslo; Communicable Disease Control; Computer Simulation; Epidemics; Public intervention; Models, Biological; infekční nemoci; lidé; Endemic equilibrium; výpočetní biologie; Systems Biology; Basic Reproduction Number; systémová biologie; Computational Biology; Switching transmission rate; počítačová simulace; Linear Models; matematické pojmy; biologické modely; epidemie; Communicable Diseases